Factors Affecting Accounting Conservatism in Manufacturing Companies Listed on The Indonesian Stock Exchange in 2017-2019 - Ni Putu Gita Pradhnya Sari; I W Karman; Istiarto Istiarto (Journal of Applied Sciences in Accounting, Finance, and Tax, 2020)
Conservatism is a precautionary principle that can be considered in accounting because a company has an uncertain or unexpected event. The purpose of this study was to determine the effect of company size, capital intensity, debt covenant, and litigation risk on accounting conservatism. This study uses secondary data in the form of annual financial statements of manufacturing companies listed on the Indonesia Stock Exchange with the study period in 2017-2019. The population in this study were 168 manufacturing companies using a purposive sampling method, there were 25 company data included in the criteria. The analysis technique used is to use multiple linear regression analysis. The results of the analysis in this study indicate that at the time of the F Test all independent variables simultaneously influence accounting conservatism, and after the T test is performed shows that company size and debt covenant variables partially affect accounting conservatism, while other independent variables do not influence conservatism accounting, manufacturing companies listed on the Indonesia Stock Exchange in 2017-2019.